Śri jhālāvaṃśavāridhi : arthāt samasta jhālākulanā itihāsa sāthe vividha vyavahārika temaja pāramārthika vishayano bhaṇḍāra - prathamāvrtti - Śukla, Nathurāma Sundarajī (s.n., 1910)
History and biographies of Jhālās, Kshatriyas from Kathiawar region, Gujarat.